SENTIMENT ANALYSIS OF TEACHER PERFORMANCE ASSESSMENT (SMKS HASSINA SUKABUMI) - Yossy Rosalinda; Slamet Sutrisno; Dana Budiman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Teacher performance assessment is an important instrument in improving the quality of education, especially at the Vocational High School (SMK) level. This study aims to analyze sentiment towards teacher performance assessment at SMKS Hassina Sukabumi using a sentiment analysis approach. Research data were obtained through surveys and reviews from students, colleagues, and school management who provided assessments of teacher performance based on pedagogical, professional, personality, and social indicators. The method used was text mining-based sentiment analysis with Orange software on qualitative data in the form of open responses, comments, and testimonials collected through interviews. The results showed that most assessments had positive sentiment, reflecting appreciation for teacher competence and dedication. However, negative sentiment was also found, indicating the need for improvements in aspects of learning innovation and technology utilization. These findings are expected to serve as a basis for school management in formulating more effective teacher professional development strategies, as well as input in the ongoing evaluation process to improve the quality of learning at SMKS Hassina Sukabumi.